Application of Project-Based Learning (PjBL) Models Assisted with Teaching Aids to Improve Students' Science Process Skills on Work and Energy Materials - Munawarah Munawarah; Nanda Novita; Faradhillah Faradhillah; Syafrizal Syafrizal; Halimatus Sakdiah (Berkala Ilmiah Pendidikan Fisika, 2023)
This research aimed to assess if MAS Syamsuddhuha's application of the PjBL model has increased the efficiency of the student's training processes. This analysis is a quasi-experimental design analysis. The subjects of this research are students from grades X IPA 4 as the experimental class and X IPA 5 as the control class. During the experiment, the experimental class used the PjBL model with teaching aids, whereas the control class used the PjBL model during the teaching process. The design method used in this study is called nonequivalent control group design. Instrumental research tools in the form of tests and observation sheets are used to observe students' science process skills. The hypothesis uses a non-parametric test for the post-test sample rate. The results showed that the post-test experimental class score was 81.19, and the control class post-test score was 66. Applying the PjBL model with teaching aids has increased students' science process skills in work and energy.